A Note on Some Ecological Aspects of the Sorghum Stem Borer in the Nuba Mountains, Sudan - Ali, Eisa Y. Adam; Ali E. (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was designed to collect some information about the sorghum stem borer in the Nuba Mountains, South Kordofan State. It was carried out during 2005/06 and 2006/07 season, to determine the population dynamics and the alternative host plants of the stem borer. Light trap was used for adult trapping, and a survey was carried out for host plants. The number of adults was low at the beginning of the season (June), gradually increased towards the end of the season (October) and the borer disappeared by the end of November. Night activity of the adults was low at 7:00 pm and increased gradually towards 10:00 pm. The highest infestation by stem borer (76%) was recorded on sorghum (Sorghum bicolor L.) followed by Sorghum arundinceum (adar) (63%), maize, Zea mays (50%) and pearl millet (33%)